Detection of potential overbreak zones in tunnel blasting from MWD data. (December 2018) - Navarro, J.; Sanchidrián, J.A.; Segarra, P.; Castedo, R.; Costamagna, E.; López, L.M.
Highlights: A new methodology is developed to calculate the area excavated on the contour perimeter by blasting effect. A normalization procedure of the MWD data is carried out to obtain rock dependent parameters. A non-linear regressive model has been developed to estimate a predicted excavated mean distance. Distinct relations between different MWD parameters and area excavated are obtained. Abstract: The damage from blasting to the remaining rock mass is analyzed with the purpose of developing a drilling index from measure while drilling (MWD) parameters, able to predict high risk of potential over- and under-excavated zones produced by blasting in the contour of a tunnel. A new methodology based on the comparison of scanner profiles of the excavated sections with the position of the contour blastholes, has been developed to obtain the excavated mean distance (EMD) between the blasthole and the excavated profiles at each MWD record position, which may be considered as a damage measure. MWD parameters, that describe the in-situ rock mass properties before the blast, are thoroughly normalized to remove external influences that may hide the actual response of the rig to rock mass properties and lead to wrong interpretations. 54 blasts, which comprise around 1700 contour blastholes, have been compared with more than 4000 excavated sections. A non-linear multiple-variable power-form model has been developed to predict the excavated mean distance as function of the normalized penetration rate, hammer pressure, rotation speed, rotation pressure and water flow parameters, and the lookout distance. These parameters combine the rotational, hydraulic and percussive mechanisms of the drill, and the confinement of the explosive charge with depth. Sources of uncertainty, unavoidable in the harsh condition in which the data were measured, such as drilling deviations, the scaling and primary support prior to scanning the excavated section, possible variations (unrecorded) in the explosive linear density, etc., have been assumed to be of random nature.